The effect of electroconvulsive therapy on autobiographical memory: a systematic review. - Fraser, L; O'Carroll, R; Ebmeier, K (2008)
OBJECTIVES: In the last 20 years, an increasing number of articles have been published about effects of electroconvulsive therapy (ECT) on memory. Here, we review autobiographical memory studies in particular because there have been conflicting reports about the extent and persistence of ECT effects and the period before treatment from which memories are most likely to be affected. METHODS: Five psychological and medical databases (MEDLINE, PubMed, PsychINFO, ScienceDirect, and Web of Knowledge) were searched from 1980 to 2007, yielding 15 studies of ECT and autobiographical memory. RESULTS: Evidence suggests that autobiographical memory impairment does occur as a result of ECT. Objective measures found memory loss to be relatively short term (<6 months posttreatment), whereas subjective accounts reported amnesia to be more persistent (>6 months post-ECT). Electroconvulsive therapy predominantly affects memory of prior personal events that are near the treatment (within 6 months). Autobiographical memory loss is reduced by using brief pulse ECT rather than sine wave-unilateral positioning of electrodes rather than bilateral-and by titrating electrical current relative to the patient's own seizure threshold. CONCLUSIONS: Further research is required to determine memory loss associated with ECT, controlling for the direct effects of the depressive state.